The Ins and Outs of Chemokine-Mediated Immune Cell Trafficking in Skin Cancer - Yam, Andrew O.; Chtanova, Tatyana (Frontiers in Immunology, 2019)
Recent studies of the patterns of chemokine-mediated immune cell recruitment into solid tumors have enhanced our understanding of the role played by various immune cell subsets both in amplifying and inhibiting tumor cell growth and spread. Here we discuss how the chemokine/chemokine receptor networks bring together immune cells within the microenvironment of skin tumors, particularly melanomas, including their effect on, disease progression, prognosis and therapeutic options.